The Impact of Internal Learning Barriers on the Participation and Academic Persistence of Indigenous Papuan University Students - Jua, Selestina Kostaria; Sumanik, Novike Bela; Obina, Wilfrida Mayasti; Reski, Andi (Lensa: Jurnal Kependidikan Fisika, 2025)
The declining academic participation and study persistence among Indigenous Papuan students at Universitas Musamus highlight a critical issue that demands thorough investigation. While various external factors have been previously examined, this study specifically focuses on internal learning barriers, which remain underexplored in the context of higher education in Papua. The aim of this research is to explore key internal constraints affecting students’ academic engagement, including motivation, comprehension of course materials, learning strategies, and personal or social disruptions. Employing a qualitative case study approach and Miles and Hubermanâ€™s interactive data analysis model, data were collected through open-ended questionnaires and semi-structured interviews with Indigenous Papuan students. The findings reveal a complex interplay of internal challenges such as low motivation, self-doubt, ineffective learning approaches, and physical or psychological discomforts that hinder studentsâ€™ learning processes. These internal barriers not only reduce classroom engagement but also negatively impact studentsâ€™ perseverance in completing their studies. The study underscores the urgent need for contextually responsive and sustained institutional support, such as academic and psychosocial mentoring programs, to foster holistic success among Indigenous Papuan university students.